GNSS-R Earth Remote Sensing from SmallSats - Carreno-Luengo, Hugo; Lin, Chun-Liang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint of the Special Issue "GNSS-R Earth Remote Sensing from SmallSats" includes a compilation of research articles concerning the pioneering NASA CYGNSS mission and potential future constellations of GNSS-R SmallSats for Earth remote sensing. This reprint is composed of different sections, covering various scientific applications such as ocean wind speed, ocean altimetry, inland water bodies, and soil moisture content. The use of GNSS-R techniques by the future constellations of SmallSats could overcome several limitations of more classical remote sensing techniques; for example, passive microwave radiometry and synthetic aperture radar. Present and upcoming GNSS-R missions include BuFeng-1, Fengyun-3 series, Spire Global and Muon Space commercial constellations, ESA's HydroGNSS and PRETTY, TASA TRITON, etc. The outcome of this reprint aims to leverage state-of-the-art procedures and techniques by present and future mission science teams.